Optimal Portfolio Formation With Single Index Method: Study on Stocks Listed in the IDX High Dividend 20 Index on the Indonesia Stock Exchange for Period 2019-2022 - Faisal, Fanny Indrayanti; Ruma, Zainal; Anwar; Budiyanti, Hety; Natsir, Uhud Darmawan (PT. Maju Malaqbi Makkarana, 2023)
This study aims to (1) find out the composition of shares that can be formed into an optimal portfolio of IDX High Dividend 20 shares listed on the IDX for the period 2019 - 2022 using the single index model. (2) Knowing the proportion of funds that must be invested in each of the IDX High Dividend 20 shares listed on the IDX for the 2019 - 2022 period which forms a portfolio. (3) Knowing the amount of return and risk from the optimal IDX High Dividend 20 portfolio recorded on the IDX for the period 2019 - 2022 using the single index model. The sample of this research is 29 company shares selected based on purposive sampling technique. Data collection techniques are carried out with documentation. Data analysis technique uses a single index model.The results of this study indicate that there are 12 company shares included in the optimal portfolio, namely ADRO of 11.9%, BBCA of 8.7%, BBRI of 2.5%, BMRI of 13.1%, LPPF of 3.5%, ITMG of 11.3%, PTBA of 0.6% , TOWR 0.5%, DMAS 2.2%, ANTM 14.5%, HEXA 25.3%, and MPMX 5.9%. The expected return that investors get from the optimal portfolio formed is 0.0279 or 2.79% per month. The portfolio risk borne by the investor on investment from the optimal portfolio is (portfolio variance of 0.0144 or 1.44% and a standard deviation of 0.12 or 12% per month.